2021
DOI: 10.1111/eje.12648
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in removable partial prosthodontics education in dental colleges of Pakistan

Abstract: Objective The objective of this study was to investigate the current trends in undergraduate teaching of removable partial prosthodontics in various dental colleges of Pakistan. Methodology A cross‐sectional study was conducted in which a questionnaire was sent by email to head of Prosthodontics department of thirty‐one dental institutes of Pakistan. The survey included multiple questions regarding current trends in removable partial prosthodontics education in undergraduate dental colleges. Results Out of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This will also help them better communicate with the dental laboratory staff after they graduate and start independent clinical practice. 8,13 Implant-supported overdentures were taught theoretically at two-thirds of the dental colleges in the current study, but 90% of the colleges did not provide any clinical experience, including observation of surgical and restorative procedures, to students in the OPDs. Lack of resources, patient affordability and time constraints were the common reasons reported in this regard.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This will also help them better communicate with the dental laboratory staff after they graduate and start independent clinical practice. 8,13 Implant-supported overdentures were taught theoretically at two-thirds of the dental colleges in the current study, but 90% of the colleges did not provide any clinical experience, including observation of surgical and restorative procedures, to students in the OPDs. Lack of resources, patient affordability and time constraints were the common reasons reported in this regard.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, it is a necessity that dental schools continue to evaluate the curricula of removable prosthodontics to make sure that recent clinical techniques and treatment modalities are being taught to undergraduate students. 13 This is of utmost importance so that they are competent to address dental health needs of CD patients after graduation from dental schools.…”
Section: Introductionmentioning
confidence: 99%
“…Rehabilitating patients with fixed prosthesis are as important a treatment modality as removable prosthesis; hence, students must be confident prior to treating such patients in their clinical years. 23 A recent international Delphi survey also reported that 96% of experts agreed to the importance of a dedicated preclinical course for fixed prosthodontics. 11 It is thus imperative that guidelines be formulated to enhance standards of preclinical prosthodontics so similar practices are carried out in all dental institutes across the country.…”
Section: Discussionmentioning
confidence: 99%